Hypolipidemic and antioxidant activities of pioglitazone in hyperlipidemic rats - Bhosale, Rama R.; Jadhav, Rakesh R.; Padwal, Sudhir L.; Deshmukh, Vinod S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes mellitus (DM) is an endocrine disorder characterized by abnormal carbohydrate, lipid and protein metabolism along with specific long-term complications which are associated with hyperlipidemia and oxidative stress. Hence, it is important to find hypoglycemic drug that improves lipid profile and reduces oxidative stress in diabetic patient. This study, therefore, was performed to investigate hypolipidemic and antioxidant potential of Pioglitazone (PIO) in hyperlipidemic rats. Methods: Hyperlipidemia was induced in normal rats by including 0.75 gm% cholesterol and 1.5 gm% bile salt in normal diet and these rats were used for the experiments. PIO hydrochloride was administered as 10 mg/kg and 30 mg/kg dose levels to the hyperlipidemic rats. Hypolipidemic activity was estimated by plasma lipid profile parameters while antioxidant potential was estimated by ascorbic acid, catalase activity, malondialdehyde and superoxide dismutase activity using standard methods. Statistical analysis was done by one way analysis of variance (ANOVA) followed by Dunnett’s test. Results: Treatment with 10 mg/kg and 30 mg/kg dose levels of PIO hydrochloride resulted in a significant decrease in serum TG and VLDL only in 30 mg/kg PIO treated group and significant increase in serum HDL in both groups, but no significant decrease in cholesterol and LDL in both PIO treated groups. PIO increased activities of catalase enzyme and concentration of malondialdehyde significantly in only 30 mg/kg PIO treated group. But there were no significant changes in the superoxide dismutase activity and ascorbic acid concentration in both PIO treated groups. Conclusions: The present study demonstrated that treatment with 10 mg/kg and 30 mg/kg dose levels of PIO hydrochloride improves the plasma lipid profile and also reduces oxidative stress in hyperlipidemic animals.